Graduate students in times of international challenges : improving spoken production in english applied to health-related areas - Pasin, D?bora Montenegro (2019)
Introduction: Knowledge society leans on the foundation of educational and research excellence. Such implication reinforces the commitment of Higher Education Institutions to establish an agenda based on the formation of global-ready students. The development of intercultural and global skills, among which communication by means of a vehicular language plays a pivotal role, allows HEIs? members to navigate international academic settings. Objective: To assess the proficiency level in spoken English of Ph.D. students in Medicine and Health Sciences, who are non-native English speakers, post-implementation of a Program for the Improvement of Spoken Production in English for Academic Purposes (ProISP-EAP). Methodology: The experiment is based on the action-oriented approach to the teaching of EAP adopting the following methodological strategies: i) needs analysis: application of explanatory questionnaires and individual interviews; ii) blended learning: face-to-face and computermediated classes and the development of a mobile learning tool to Standard American English pronunciation exercise of general and specialized vocabulary retrieved from texts representative of participants? ongoing Ph.D. research projects; iii) spoken-oriented production: individual presentations recorded on video for evaluation. ProISP-EAP was applied to seven Ph.D. students in Medicine and Health Sciences. Assessment instruments included adapted scales from the Common European Framework of References for Languages (CEFR). Data were analyzed using triangulation methods. Results: Data reveal that partakers? spoken production in EAP was improved following ProISP-EAP application to health-related areas as participants progressed one proficiency level up the adapted Global Scale (CEFR). Conclusion: ProISP-EAP intervention improves the proficiency level of participants? spoken production in EAP.